The Go Ahead Boys and the Mysterious Old House - Kay, Ross (Salt Lake City, UT : Project Gutenberg, 2011)
"The Go Ahead Boys and the Mysterious Old House" by Ross Kay is a children$1 (Bs adventure novel likely written in the early 20th century. The story revolves around a group of four boys$1 (BGeorge Sanders, Fred Button, John Clemens, and Grant Jones$1 (Bwho are affectionately known as the Go Ahead Boys. The narrative invites readers to join their journey as they explore an old, supposedly haunted house in the countryside, sparking curiosity and bravery in the face of local myths and legends. The beginning of the book introduces the boys as they discuss the old Meeker House, known in their community for being haunted. Prompted by George's recounting of his own spooky experience at the house, the boys decide to investigate further despite their initial fears. As they approach the eerie dwelling, they encounter strange noises and bizarre occurrences that fuel their anxiety. A series of humorous exchanges among the boys and their interactions with Uncle Sim, the family$1 (Bs longtime employee, add depth to their adventure, setting the stage for the unfolding mystery and excitement that promises to follow. (This is an automatically generated summary.)s
Release date is 2011-04-25
E-text prepared by Roger Frank, Juliet Sutherland, and the Online Distributed Proofreading Team (http://www.pgdp.net)
Keywords: Mystery fiction; Haunted houses -- Juvenile fiction